Context, engagement, and the (multiple) functions of negativity bias. Issue 3 (27th June 2014) - Federico, Christopher M.; Johnston, Christopher D.; Lavine, Howard G.
Abstract Hibbing and colleagues argue that political attitudes may be rooted in individual differences in negativity bias. Here, we highlight the complex, conditional nature of the relationship between negativity bias and ideology by arguing that the political impact of negativity bias should vary as a function of (1) issue domain and (2) political engagement.